Numerical Analysis of Rotating Pumping Flows in Inter-Coil Rotor Cavities and Short Cooling Grooves of a Generator - Wei Tong (International Journal of Rotating Machinery)
An important characteristic of wall rotating-driven flows is the tendency of fluid with high angular momentum to be flung radially outward. For a generator, the rotor rotating-driven flow, usually referred to as the rotating pumping flow, plays an important role in rotor winding cooling. In this study, three-dimensional numerical analyzes are presented for turbulent pumping flow in the inter-coil rotor cavity and short cooling grooves of a generator. Calculations of the flow field and the mass flux distribution through the grooves were carried out in a sequence of four related cases Under an isothermal condition: (a) pumping flow, which is the self-generated flow resulted from the rotor pumping action; (b) mixing flow, which is the combination of the ventilating flow and pumping flow, under a constant density condition; (c) mixing flow, with density modeled by the ideal gas law; and (d) mixing flow, with different pressure differentials applied on the system. The comparisons of the results from these cases can provide useful information regarding the impacts of the ventilating flow, gas density, and system pressure differential on the mass flux distribution in the short cooling grooves. Results show that the pumping effect is strong enough to generate the cooling flow for rotor winding cooling. Therefore, for small- or mid-size generators ventilation fans may be eliminated. It also suggests that increasing the chimney dimension can improve the distribution uniformity of mass flux through the cooling grooves.